Pengaruh Pemberian N-Asetilsistein dan Vitamin D Terhadap Kadar Interleukin-1β Pada Otitis Media Supuratif Kronis - Dewi, Pratiwi; Gayatri, Astrid (PERHATI-KL, 2024)
Background: Chronic suppurative otitis media (CSOM) is a major health problem in many populations around the world, causing significant morbidity and mortality. It is characterized by transformation and hyperplasia of the middle ear mucosa following infiltration of numerous inflammatory cells. Recent researches showed a significant impact of the anti-inflammatory and anti-oxidant effects of N-Acetylcysteine (NAC) and vitamin D independently, but their role in the pathophysiology of CSOM was still unclear. Purpose: To evaluate the effect of NAC and vitamin D supplementation on vitamin D and interleukine-1β levels in CSOM. Method: The research was an experimental study with randomized controlled trial design, and was conducted at ENT polyclinic, Dr Moewardi Regional General Hospital Surakarta on May-October 2023. Blood serum examination of vitamin D and IL-1β levels was done at Biomedical Laboratory of Medical Faculty Sebelas Maret University. Result: There were 36 CSOM subjects without cholesteatoma who met the inclusion and exclusion criteria. The NAC+vitamin D group had the highest mean vitamin D level (30.82±5.35 ng/mL) and the lowest mean IL-1β level (23.81±7.13 pg/mL) compared to the control group and the group that received only NAC or vitamin D alone. (p<0.05). Conclusion: N-Acetylcysteine and vitamin D supplementation had a synergistic effect in reducing oxidative stress and inflammation in CSOM.